Ralstonia mannitolilytica bacteremia in a maintenance hemodialysis patient - Subramanian, Sreevidya; Rajkumar, S Venkatesh; Thirunarayan, M A; Samal, Debashree (Eastern Journal of Medical Sciences, 2016)
Ralstonia mannitolilytica is a nonfermentative, Gram-negative bacterium isolated infrequently from clinical samples. It is widelydistributed in nature, being a frequent contaminant in water supplies. It is increasingly identified as an opportunistic pathogen innosocomial infections, especially among immunosuppressed patients. It has also been implicated in common source nosocomialinfection outbreaks due to the addition of contaminated water to parenteral fluids and to medical equipment presumed to besterile. True bacteremia with the organism, however, cannot be ruled out, especially if it is isolated repeatedly from the samepatient within 3 successive days from blood cultures. A 22-year-old Ethiopian male presented to us in December 2015 with feverwith chills and rigor, vomiting, and headache. He was a known end-stage renal disease patient on thrice per week hemodialysisthrough a tunneled hemodialysis catheter for the past 1 year. He had an episode of catheter-related blood stream infection inOctober-November 2015 and was treated at a multispeciality hospital with parenteral antibiotics (piperacillin-tazobactam) for2 weeks (for growth of Pseudomonas aeruginosa in blood cultures) during the same admission phase. The tunneled catheter wasnot removed then and lock therapy was used and the patient improved gradually with antibiotics. During the current admission,three blood culture sets (aerobic and anaerobic), one set from the dialysis line and two from the peripheral lines were submittedto microbiology laboratory. Blood cultures (one bottle from each of the three sets) flagged positive. The blood culture sentfrom the hemodialysis line was the first to flag positive 12 h after it was loaded onto the BACTEC 9050 system. This wasfollowed by the aerobic and anaerobic bottles from the peripheral lines. The preliminary Gram-stain showed Gram-negativebacilli and the cultures grew Gram-negative organisms. The organism was identified as R. mannitolilytica by the Vitek 2C.Disc diffusion (CLSI, 2015) was done for the various antibiotics, and there was a 6 mm resistant zone for the following paneltested: Gentamicin, cotrimoxazole, aztreonam, amikacin, ceftriaxone, cefotaxime, cefepime, ceftazidime, and carbapenems; theorganism was intermediate to piperacillin-tazobactam (17 mm) and was sensitive to and cefoperazone-sulbactum (23 mm). In ourset up, this was the first case of R. mannitolilytica isolated as a significant pathogen in a case of true bacteremia. R. mannitolilyticacan thus cause true bacteremia as well in addition to just being an environmental contaminant. Early recognition of the infectionhelps in instituting appropriate antibiotic with complete resolution of the infection. In our case report, the prompt report ofmicrobiology department enabled us to treat the patient on time with appropriate antibiotic and also prevented the prematureremoval of the tunneled catheter. The problems caused by this bacterium occur rapidly and disease progression is fast; therefore,R. mannitolilytica infections should draw sufficient attention from clinical physicians and bacteriology workers to respond to theresulting severe consequences.